Pengaruh Citra Merek dan Harga terhadap Keputusan Pembelian Pada PT Indonesia Comnets Plus (Icon+) Area Jakarta Timur - Surya Budiman; Budi Ismanto; Ahyani Ahyani; Dewi Ningsi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
In the increasingly competitive telecommunications service industry, brand image and pricing strategy play an important role in shaping organizational purchasing decisions. This study aims to analyze the effect of brand image and price on purchasing decisions at PT Indonesia Comnets Plus (Icon+) East Jakarta Area, both partially and simultaneously. This research uses a quantitative associative approach. The sample consisted of 100 respondents determined using the Slovin formula and selected through simple random sampling. Data were collected through questionnaires using a Likert scale and analyzed using SPSS version 26 with multiple linear regression analysis. The results indicate that both brand image and price have a positive and significant effect on purchasing decisions, either individually or jointly. A stronger brand image and more appropriate pricing are proven to increase purchasing decisions. Together, these variables explain a considerable proportion of the variation in purchasing decisions, while the rest is influenced by other factors outside the model. Therefore, companies are encouraged to strengthen brand image management and implement competitive pricing strategies to improve purchasing decisions. In addition, future studies are recommended to include other variables such as service quality, promotion, and customer experience to provide a more comprehensive understanding of consumer behavior in the telecommunications service sector, particularly at the corporate level in Indonesia.